2020
DOI: 10.5194/acp-20-6095-2020
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of brown carbon onto snow: changes in snow optical and radiative properties

Abstract: Abstract. Light-absorbing organic carbon aerosol – colloquially known as brown carbon (BrC) – is emitted from combustion processes and has a brownish or yellowish visual appearance, caused by enhanced light absorption at shorter visible and ultraviolet wavelengths (0.3 µm≲λ≲0.5 µm). Recently, optical properties of atmospheric BrC aerosols have become the topic of intense research, but little is known about how BrC deposition onto snow surfaces affects the spectral snow albedo, which can alter the resulting rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 118 publications
(177 reference statements)
2
20
0
Order By: Relevance
“…BrC forcing was enhanced by 167% when black carbon and dust are in snowpack. This value is in line with Beres et al (2020), where a reduction of local BrC RF of about a factor of 2 is found, when the species is added to a dark snowpack. Finally, dust RF increased by 92% in OSPT simulation.…”
Section: Discussion Of Uncertaintiessupporting
confidence: 89%
“…BrC forcing was enhanced by 167% when black carbon and dust are in snowpack. This value is in line with Beres et al (2020), where a reduction of local BrC RF of about a factor of 2 is found, when the species is added to a dark snowpack. Finally, dust RF increased by 92% in OSPT simulation.…”
Section: Discussion Of Uncertaintiessupporting
confidence: 89%
“…The U samples had the highest number of assigned compounds among four groups of sites in both ESI+ and ESI− with averages of 1113 ± 203 and 871 ± 287, respectively (Tables 1 and 2), whereas the number of as-signed species from S samples was lowest (mean: 727 ± 146 and 438 ± 84 for ESI+ and ESI− modes, respectively), reflecting the high molecular complexity of U samples. The numbers of assigned formulas in this study are comparable to the assignments reported for urban aerosol samples (∼ 800-1800) (Lin et al, 2012;Wang et al, 2017a) and WSOC of LHG glacier from the TP region (∼ 700-1900) (Feng et al, 2016(Feng et al, , 2018, but they are lower than those of WSOC from the Antarctic (∼ 1400-2600) and Greenland ice sheets (∼ 1200-4400) (Antony et al, 2014;Bhatia et al, 2010). The mass spectrum plots constructed from individual samples showing integrated composition of U, R, S, and site 120 samples along with the corresponding number contributions from different formula categories are shown in Fig.…”
Section: General Hrms Characteristicssupporting
confidence: 84%
“…Correlative analysis of these multimodal data sets facilitates the comprehensive characterization of chromophores present in complex environmental mix-tures (Laskin et al, 2015;Lin et al, 2016Lin et al, , 2018Wang et al, 2020a). Presently, HRMS studies of WSOC existing in the cryosphere are still limited to the snow-ice in polar regions (Antony et al, 2014(Antony et al, , 2017Bhatia et al, 2010) and mountain glaciers in the Alps (Singer et al, 2012) and on the TP (Feng et al, 2016;Spencer et al, 2014;L. Zhou et al, 2019) with perennial snowpack.…”
mentioning
confidence: 99%
“…It is parameterized through default and customizable user inputs of sky conditions (spectral direct or diffuse incident radiation, solar zenith angle, incident spectral radiance profile), snowpack properties (layer thickness, grain effective radius, mass density, underlying surface albedo), and aerosol characteristics (type and mass mixing ratio). All of the input parameters can be modified to suit the user's needs, such as defining a non-default surface spectral irradiance, redefining the optical properties of ice (e.g., Singh and Flanner [18]), or adding optical properties for custom impurities-such as brown carbon [19] and snow algae [20]. Standalone SNICAR code is available for multi-layer simulations as MATLAB (The MathWorks, Inc., Natick, MA, USA) code or as a web-based, single-layer simulator (both available from http://snow.engin.umich.edu).…”
Section: Snow Ice and Aerosol Radiation (Snicar) Model And Codementioning
confidence: 99%